Extraction and Determination of Amygdaline in Iraqi Plant Seeds Using the Combined Simple Extraction Procedure and High-Performance Liquid Chromatography (Baghdad Science Journal, 2013)
Abstract :In this study, amygdaline in Iraqi plant seeds was extracted and isolated from their seeds matrix using reflux procedure and subsequently identified and determined by high performance liquid chromatography (HPLC) on reversed phase column of LC-18 (150mm x 4.6mm, 5?m )with actonitrile :water ( 50 : 50 ) as mobile phase at flow rate of ( 0.5 mL/min ) and detection at wavelength of 215 nm.The experimental results indicated that the linearity of calibration is in the range of 1.0-30.0 mg L-1amygdaline with the correlation coefficient of 0.9949. The limit of detection (LOD) and limit of quantitation (LOQ) for amygdaline were of 0.88 and 2.93 mg L-1 in standard pure sample. The mean recovery percent is 97.34±0.58 at 95% confidence interval and relative standard deviation in the range of 1.19-2.08 %. The content of amygdaline in plant samples was 4.60± 0.47 g /100 g, and 0.27±0.029 g/100g of apricot and citrullus colocynth respectively.